Multiple Resistance Mechanisms to Tyrosine Kinase Inhibitors in EGFR Mutated Lung Adenocarcinoma: A Case Report Harboring EGFR Mutations, MET Amplification, and Squamous Cell Transformation - Bruno, Rossella; Del Re, Marzia; Cucchiara, Federico; Petrini, Iacopo; Alì, Greta; Crucitta, Stefania; Proietti, Agnese; Valleggi, Simona; Chella, Antonio; Danesi, Romano; Fontanini, Gabriella (Frontiers in Oncology, 2021)
Resistance to EGFR tyrosin kinase inhibitors (TKI) inevitably occurs. Here it is reported the case of a young patient affected by lung adenocarcinoma harboring the L858R EGFR sensitive mutation. The patient developed multiple TKI resistance mechanisms: T790M EGFR resistance mutation, detected only on tumor cell-free DNA, squamous cell transformation and MET amplification, both detected on a tumor re-biopsy. The co-occurrence of squamous cell transformation and de novo MET amplification is an extremely rare event, and this case confirms how dynamic and heterogeneous can be the temporal and spatial tumor evolution under treatment pressure.